Development of an IoT-Based (LoRaWAN) Tractor Tracking System - Çağdaş Civelek (Journal of Agricultural Sciences)
The use of new technologies and precision agriculture (PA) in farms has become more important due to the need for enough agricultural production for increasing world population opposed to decreasing farm areas. PA covers wide range of technologies like sensors, microcontroller-based devices, machine to machine communication technologies, global positioning systems but, the investment costs of these devices are literally expensive which become a constraint for farmers especially in developing countries. Internet of things (IoT) technology is a new era that agricultural production will be the one area mostly affected by. LoRaWAN is one of the new communication technologies for IoT which enables almost everything on the planet to be connected to internet and deliver high amount of data with no expense. In this research by using the advantages of LoRaWAN, a new IoT-based tractor tracking system including a LoRaWAN module and a web-based software was developed, and the test results were evaluated. As a result, it was found that the developed system was capable of measuring and sending tractor sensor data along with geospatial position of the tractor and serving the data on the web-based user interface.